Relationship of the Use of Mother Tongue-Based Multilingual Education to the English Learning Competencies of Pupils - Tadeo, Gretchen P; Queroda, Dr Phillip G (ASEAN Journal of Basic and Higher Education, 2020)
This study was conducted to find the relationship of the Mother Tongue Based Multilingual Education (MTB-MLE) to the acquisition of the English learning competencies of the Grade 4 pupils. Specifically, it identified the level of acquisition of the English learning competencies as perceived by the teachers across the following domains: listening comprehension, oral language, vocabulary development, reading comprehension, oral reading fluency, study strategy, grammar, writing composition and attitude and its relationship across pupils profile variables. The descriptive type of research was used in this study and was anchored on the Second Language Acquisition (SLA) Theories. The data were gathered through the use of a questionnaire. The information gathered were tabulated and analyzed using the frequency counts, percentage, weighted mean, rank, chi-square statistics and Pearson r Correlation. The study found out that the Grade 4 pupils moderately acquired all the English learning competencies with regards to the given. Only oral reading fluency competencies are found to be related to age and with regards to pupils’ sex vocabulary development, grammar and attitude learning competencies show significant relationship. It also disclosed that vocabulary development, grammar, writing composition and attitude learning competencies are related with the pupils’ parents’ monthly income. While there is significant relationship between listening comprehension and writing composition learning competencies and pupils’ mother tongue. Lastly, results in this study showed that all the English competencies turned out to be highly related with the pupils’ mother tongue grade. Hence, there is a dependence between the pupils’ mother tongue grade and English competencies.